Legal Protection Practice For Children Of Terrorists At Al-Hidayah Islamic Boarding School In Deli Serdang Regency Analysis Of Indonesian Government Regulation Number 78 Of 2021 - Fahmi Aditya Hafidz Lubis; Nurul Huda Prasetiya; Arifuddin Muda Harahap (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The research focus is on the legal protection of children from perpetrators of terrorist crimes, regarding how the handling of children of terrorist crime perpetrators is carried out through a justice-oriented approach and analysis based on Indonesian Government Regulation No. 78 of 2021 concerning Special Protection for Children, and its implementation at Al-Hidayah Islamic Boarding School in Deli Serdang Regency. The research problem formulated in this study is how the concept of legal protection for children is defined according to Indonesian Government Regulation No. 78 of 2021 concerning Special Protection for Children. The research model is qualitative, and the preliminary steps involve field observations and interviews. This study employs legal state theory and legal protection theory. In conclusion, this research demonstrates that the legal protection practices for children of terrorist crime perpetrators at Al-Hidayah Islamic Boarding School in Deli Serdang Regency have provided partial legal protection to these children and warrant maximum improvement. This improvement could be achieved through the collaboration of various institutions such as the Ministry of Religious Affairs, Ministry of Social Affairs, Ministry of Women's Empowerment and Child Protection, National Counterterrorism Agency (BNPT), and other relevant agencies. These institutions should focus on providing services in the areas of education, ideology, and national values; counseling about the dangers of terrorism; social rehabilitation; social support and the necessity of other concrete regulations aimed at child protection. For instance, regulations could ease the administrative processes for former terrorism perpetrators and their families.